Cecropin B loaded TiO2 nanotubes coated with hyaluronidase sensitive multilayers for reducing bacterial adhesion. (15th February 2016) - Shen, Xinkun; Zhang, Fei; Li, Ke; Qin, Chenhu; Ma, Pingping; Dai, Liangliang; Cai, Kaiyong
Abstract: Bacterial infection, a common issue related to orthopedic implantation, is regarded as the second dominant factor resulting in implantation failure. To address the issue, the study reports a novel antibacterial titanium substrate against hyaluronidase secreting bacterium of Staphylococcus aureus, which was fabricated by employing TiO2 nanotubes (TNTs) to load cecropin B (CecB), and then coating with hyaluronidase sensitive multilayers of chitosan/sodium hyaluronic-cecropin B [(Chi/SH–CecB)5 ] onto the titanium surfaces via layer by layer technique (TNT–CecB–LBLc). Fourier transform infrared spectroscopy (FITR) and nuclear magnetic resonance ( 1 H NMR) characterizations proved the successful synthesis of SH–CecB. Scanning electron microscopy (SEM), atomic force microscopy (AFM), fluorescence microscopy and water contact angle measurements verified the formation of multilayers onto CecB loaded titanium substrates. The presence of S. aureus and/or exogenous hyaluronidase effectively triggered the degradation of multilayers, thus facilitating the release of CecB from TNTs. The antibacterial evaluations proved that TNT–CecB–LBLc substrates had good early (4 h) and long term (72 h) antibactericidal capacity against both S. aureus and Staphylococcus epidermidis . Moreover, the cellular tests displayed that TNT–CecB–LBLc substrates had relatively good cytocompatibility for osteoblasts, even co-culture with S. aureus . The study provides new insight into the development of bacteria-mediated antibacterial implants for orthopedic application. Graphical abstract: Highlights: Hyaluronidase sensitive titanium substrates are designed and constructed. Degradation of multilayers is accelerated by hyaluronidase-secreting bacteria. The loaded drug is quickly released once Staphylococcus aureus infection occurs. The above system shows good cytocompatibility and bactericidal ability.